2013
DOI: 10.1017/s1460396913000277
|View full text |Cite
|
Sign up to set email alerts
|

An overview of augmented and virtual reality applications in radiotherapy and future developments enabled by modern tablet devices

Abstract: Purpose: We review augmented (AR) and virtual reality (VR) applications in radiotherapy as found in the scientific literature and highlight future developments enabled by the use of small mass-produced devices and portability of techniques developed in other fields to radiotherapy.Analysis: The application of AR and VR within radiotherapy is still in its infancy, with the notable exception of training and teaching applications. The relatively high cost of equipment needed to generate a realistic 3D effect seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…There is no doubt that the use of MR can assist in a variety of patient treatment scenarios. Radiotherapy treatment is one example and Cosentino et al [19] have provided a recent review. Most of the studies identified in this specialty area indicate that MR in radiotherapy still needs to address limitations around patient discomfort, ease of use and sensible selection and accuracy of the information to be displayed, although the required accuracy for most advanced radiotherapy techniques is of the same order of magnitude as that which is already being achieved with MR.…”
Section: Applications 41 Treatmentmentioning
confidence: 99%
“…There is no doubt that the use of MR can assist in a variety of patient treatment scenarios. Radiotherapy treatment is one example and Cosentino et al [19] have provided a recent review. Most of the studies identified in this specialty area indicate that MR in radiotherapy still needs to address limitations around patient discomfort, ease of use and sensible selection and accuracy of the information to be displayed, although the required accuracy for most advanced radiotherapy techniques is of the same order of magnitude as that which is already being achieved with MR.…”
Section: Applications 41 Treatmentmentioning
confidence: 99%
“…There are numerous VE systems and applications reported in the literature. Readers who are interested in exploring the broad spectrum of VEs may consult a number of books and literature surveys on the subject [SCS01,Vin13] as well as in specific areas, including, but not limited to, presence [SvKv01,SSU13], haptics [CMJ11], augmented reality [ABB * 01, SFN08], usability evaluation [BGH02], medicine and healthcare [ALF * 11, CJV13,WKL16], flight simulation [Lee05,RS08], education [BFT16], sports [CPW * 12], and cultural and natural heritage [Add00].…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, the application of optical see-through head-mounted displays has significantly increased with the advancements in augmented reality (AR) technology [1][2][3][4]. OST-HMDs are crucial AR devices that overlay virtual objects onto the user's real-world field of view through transparent displays, providing users with immersive augmented reality experiences.…”
Section: Introductionmentioning
confidence: 99%